é€šè¿‡è¡¨æ¼”æ¸¸æˆæé«˜ä»¥é©¬å†…åˆ©åˆä¸äºŒæ ¡äºŒå¹´çº§å¦ç”Ÿçš„æ±‰è¯å£è¯èƒ½åŠ› - Ereen, .; Thamrin, Lily; ., Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
????????????????????????????????????????????C???????39??????14????25?????????????????????????????????????????????????????????????????????????????????????? ???????????????? Abstract?The purpose of this research is to help the students through game teaching method improve, to know that if it can increase the students ability  the students speaking mandarin ability. The object of this research are students of the two grade of Junior High School Kristen Immanuel 2, C class one, with total students were 39 students (14 male; 25 female). The research method are practice classroom teaching methods,look into questionnaire methode and method of test . Based on analysis of the teaching learning process in the classroom and the result in pre-test and post-test, the writer gets that result the students before Chinese subject is not interesting and interesting now,more dare to speak Chinese,said Chinese fluent.   Keywords:  Speak Chinese Languange; Game; Role Playing Game